The influence of ethical leadership on teaching performance in public higher learning institutions - Elias Mseti (Universitas Airlangga, 2023)
Employee performance is often problematic in the competition of organizations in a globalization and industrialization era. The purpose of this research is to investigate how ethical leadership influences teaching effectiveness in Tanzania's Public Higher Learning Institutions. The study focuses on how academic staff teaching performance is affected by role clarification and integrity. The study's target population includes 4,863 academic staff members at public HLIs in Tanzania, and 350 respondents were chosen from this group using a stratified simple random selection technique. Employees at public HLIs are bound to an ethical code of conduct and ethical values, and they are required to perform better so that the entire community can obtain high-quality educational services. Employee performance, on the other hand, is mediocre. A lack of required resources, inadequate leadership, low employee motivation, role ambiguity, and a lack of ethical guidance cause unsatisfactory performance; nevertheless, it is uncertain how much ethical leadership influences employee performance in teaching. The information was acquired by a self-administered questionnaire with closed-ended questions, and it was statistically examined through regression analysis. The findings show that role clarification and integrity have a positive impact on employees' performance in teaching in HLIs. HLI's leadership should take the lead in fostering ethical leadership among its employees by complying with laws and regulations (ethics codes).